2021
DOI: 10.1002/celc.202100543
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Reduction Reaction at Single‐Site Catalysts: A Combined Electrochemical Scanning Tunnelling Microscopy and DFT Investigation on Iron Octaethylporphyrin Chloride on HOPG**

Abstract: Here, we investigate the electrochemical activity of a highly oriented pyrolytic graphite (HOPG) supported iron octaethylporphyrin chloride film as a working electrode for the oxygen reduction reaction in 0.1 M HClO4 electrolyte. A voltammetric investigation indicated a quasi‐reversible electron transfer for the FeIII/FeII redox process, which turned out to be responsible for a “redox catalysis like” mechanism, in which the reduction of the metal center is first required to allow the O2 reduction. Here we prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 56 publications
(58 reference statements)
0
13
0
Order By: Relevance
“…All the measurements were done in a three-electrode cell thermostated at 25 °C. The RRDE tip was used as the working electrode, a graphite rod was used as the counter electrode, and for the acidic electrolyte, a homemade RHE as the reference electrode was prepared before each experiment according to the literature procedure …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All the measurements were done in a three-electrode cell thermostated at 25 °C. The RRDE tip was used as the working electrode, a graphite rod was used as the counter electrode, and for the acidic electrolyte, a homemade RHE as the reference electrode was prepared before each experiment according to the literature procedure …”
Section: Methodsmentioning
confidence: 99%
“…Hydrogen-related technologies represent a crucial field for moving to a low-carbon economy, which is expected to offer promising opportunities not only to fight climate change but also to enhance energy delocalization and safety, to revolutionize the transport sector both for goods and people and to develop local industries in many countries. , A clear evidence of this interest is proven by the enormous investments made in both Europe and in the United States for the development of hydrogen-based technologies, including fuel cells. The high cost of these devices is due to the slow kinetics of the oxygen reduction reaction (ORR) at the cathode side, and so the use of Pt-based materials as catalysts is still required. With their low cost, high availability, and good tolerance to poisoning, non-PGM is the best known alternative to Pt. , During past decades, various non-PGM catalysts were investigated: M–N–C based on porphyrin-like M–N x sites, non-precious metal oxide, chalcogenides, oxynitrides, and carbon oxynitrides . Among others, the most interesting and active are M–N–C with Fe metal center, where iron could coordinate from two up to five nitrogen functional groups, with the metal porphyrin-like Fe–N 4 site considered as the most important for the selectivity and activity in ORR. , A good catalyst is the result of a combination of several aspects like the site density, the intrinsic activity of sites, the carbon support hierarchical structure, the surface chemistry, the graphitization degree, and so forth. Choosing the right carbon matrix is the turning point to improve catalytic performance. Indeed, increasing the density of the active sites is not sufficient to enhance the catalyst activity since it is also necessary to rationally design the textural and porous properties of the carbon support to facilitate the mass transport between micropores and the bulk solution. ,, Moreover, the catalytic enhancement can be obtained by the incorporation of heteroatoms like N, S, P, or B or another metal to form a bimetallic system. , …”
Section: Introductionmentioning
confidence: 99%
“…The reference electrode was a reversible hydrogen electrode (RHE), which was freshly prepared before each experiment as reported in the literature. [ 58 ] A graphite rod was used as a counter electrode, whereas a GC‐disk (5 mm diameter) ‐ Pt‐ring RRDE was used as a working ‐ H 2 O 2 sensor electrode. The electrochemical characterizations were performed on a thin film catalyst layer obtained by drop‐casting the catalyst ink on the GC disk of the RRDE, with a catalyst loading of 600 μg cm −2 .…”
Section: Methodsmentioning
confidence: 99%
“…Despite the economic and technological problems related to the production, transport, and storage of hydrogen, the main FCs problem is on a different aspect: the high cost due to the low kinetic of the cathode reaction, the oxygen reduction reaction (ORR), and thus, the usage of Pt-based materials as catalysts is still required. With their low cost, high availability, and good tolerance to poisoning, non-precious-metal catalysts (non-PGM) are the best known alternative to Pt. During past decades, various non-PGM catalysts were investigated: M–N–C based on M–N x sites, non-precious-metal oxide, chalcogenides, and oxynitrides . The most studied are M–N–C, and among them, the most active metal center is Fe, where iron coordinate from two to five nitrogen functional groups, and among the different types of Fe–N x ( x = 1–5), the metal porphyrin-like Fe–N 4 site is considered the most important for its ORR selectivity and activity. However, different factors need to be considered to reach good performances, including site density, carbon support hierarchical structure, surface chemistry, graphitization degree, etc. Choosing the right carbon matrix is the turning point to improve catalytic performance; in fact, the increment of the active SD is per se not enough to enhance the activity, but it is necessary to rationally design the textural and porous properties of the carbon matrix to facilitate the mass transport between micropores and the bulk solution. ,, Moreover, it has been also demonstrated that the incorporation of heteroatoms can influence the catalytic performances . The idea underlying the doping process is the capability of heteroatoms to modulate the electronic structure of the carbon plane via the delocalization of the π-electrons when pinned into the carbon framework, improving the catalyst activity .…”
Section: Introductionmentioning
confidence: 99%